محددات الرشاقة الاستراتيجية وعلاقتها بالتميز الإداري بالاتحاد المصري للسباحة - عبدالحافظ، مؤمن طه عبدالنعيم (جامعة بني سويف - كلية التربية الرياضية, 2021)
التعرف على العلاقة بين محددات الرشاقة الاستراتيجية والتميز الإداري بالاتحاد المصري للسباحة، من خلال الإجابة على التساؤلات التالية. ما محددات الرشاقة الاستراتيجية بالاتحاد المصري للسباحة؟ ما مستوى التميز الإداري بالاتحاد المصري للسباحة؟ ما العلاقة بين محددات الرشاقة الاستراتيجية والتميز الإداري بالاتحاد المصري للسباحة؟ واستخدم الباحث المنهج الوصفي، وكانت عينة البحث (27) فرد من أعضاء مجلس الإدارة والإداريين بالاتحاد المصري للسباحة، واستخدم الاستبيان كأداة لجمع البيانات، إحداهما للتعرف على واقع الرشاقة الاستراتيجية بالاتحاد المصري للسباحة والآخر للتعرف على مستوى التميز الإداري بالاتحاد المصري للسباحة، وكانت أهم النتائج توجد علاقة ارتباطية موجبة دالة إحصائيا بين محددات الرشاقة الاستراتيجية والتميز الإداري بالاتحاد المصري للسباحة.
Identify the relationship between the determinants of strategic agility and administrative excellence in the Egyptian Swimming Federation, by answering the following questions. What are the determinants of strategic agility in the Egyptian Swimming Federation? What is the level of administrative excellence in the Egyptian Swimming Federation? What is the relationship between the determinants of strategic agility and management excellence in the Egyptian Swimming Federation? The researcher used the descriptive approach, and the research sample was (27) members of the board of directors and administrators of the Egyptian Swimming Federation, and used the questionnaire as a tool for data collection, one of them to identify the reality of strategic agility in the Egyptian Swimming Federation and the other to identify the level of administrative excellence in the Egyptian Swimming Federation, and the most important results were found A positive, statistically significant correlation between the determinants of strategic agility and managerial excellence in the Egyptian Swimming Federation.
Keywords: الإدارة الرياضية -- التخطيط الاستراتيجي -- إدارة التميز -- الرياضات المائية -- مصر